EFFICIENCY AND BASES OF CALCULATION OF HEAT HYDROPERCUSSION DEVICES - I. A. Semenova (Вестник СибАДИ, 2017)
This article presents the results of research and the definition of efficiency of hydraulic device used as a replacement of the working body of the excavator. Dependences for determining efficiency of hydraulic devices, as well as formulas for determining the amount of heat isolated and retracted during operation of hydraulic devices. The article shows the dependence of the main parameters of hydraulic hammers devices depending on the properties and parameters of the developed soil base machine.